Determinants of Fertility Desire among Women Living with HIV in the Childbearing Age Attending Antiretroviral Therapy Clinic at Jimma University Medical Center, Southwest Ethiopia: A Facility-Based Case-Control Study - Aylie, Nigusie Shifera; Dadi, Lelisa Sena; Alemayehu, Eshetu; Mekonn, Mengistu Ayenew (International Journal of Reproductive Medicine, 2020)
Background. High fertility and aspiration to have more children are a normal phenomenon in many developing countries including Ethiopia. The desire of people living with HIV/AIDS (PLWHA) to have children can have significant public health implications. Despite the growing number of women living with HIV/AIDS, the issues of fertility and childbearing intention have not been widely studied in Ethiopia. Objective. To identify determinants of fertility desire among women living with HIV in the childbearing age attending antiretroviral therapy clinic at Jimma University Medical Center, Southwest Ethiopia. Methods. A facility-based case-control study was conducted in March 2019. Cases were women living with HIV who had fertility desire, and controls were those who had not. Data was collected using a face-to-face interview using a pretested questionnaire. The data was entered into EpiData 3.1 and exported to SPSS Version 24 for analysis. Bivariate and multivariable logistic regression analyses were used to identify candidate and independent determinants of fertility desire, respectively. Independent determinants associated with fertility desire were assessed using AORs with their corresponding 95% CIs at P value < 0.05 cutoff point. Results. Three hundred forty-four (115 cases and 229 controls) were included into the study with a 100% response rate. Age categories 15-24 (AOR: 4.1; 95% CI: 2.0, 8.4) and 25-34 (AOR: 2.3; 95% CI: 1.3, 4.2) years, not using family planning (AOR: 2.3; 95% CI: 1.4, 4.0), and having a sexual partner (AOR: 1.9; 95% CI: 1.1, 3.2) were independent predictors of fertility desire. Conclusions. Age of women, family planning, and sexual partner were found to be the independent predictors of fertility desire among women living with HIV/AIDS. Policymakers and health care providers who are working on an ART clinic should try to consider the effects of these factors for women living with HIV while developing HIV/AIDS interventions and discussing on sexual and reproductive health issues with their clients, respectively.